Three-dimensional bioprinting of bioactive scaffolds with thermally embedded abalone shell particles for bone tissue engineering - Dahong Kim; Jihye Lee; Ji Min Seok; Joo-Yun Jung; Jun Hee Lee; Jun Sik Lee; Kangwon Lee; Su A Park (Materials & Design, 2021)
Abalone shells, which contain both organic and inorganic matter, can facilitate bone remodeling and have been used to fabricate three-dimensional (3D)-printed scaffolds for bone regeneration. Herein, polycaprolactone (PCL) scaffolds were fabricated using 3D printing with abalone shell particles (ASPs) used in high-temperature processing. ASPs were heated to approximately the melting point of PCL and thermally embedded in 3D-printed PCL using a relatively simple process. The morphology and roughness of the composite scaffold changed according to the weight of ASPs used. The scaffolds were grouped as follows: ASP25 (25 mg), ASP50 (50 mg), and ASP100 (100 mg). The ASP25 group exhibited optimum cell viability and proliferation because of the direct influence of roughness and rapid pH changes. The ASP25 and ASP100 groups showed the highest alkaline phosphatase activity. This could be attributed to the effect of the alkaline environment, dissolution of calcium ions, and presence of bioactive molecules in the ASPs that could support bone regeneration. Therefore, the ASP25 group was the most suitable for fabricating bone scaffolds. This study revealed the potential applicability of ASP-embedded scaffolds in bone tissue engineering involving natural bio-organisms that self-mineralize in a process similar to human bone formation.